2013
DOI: 10.1093/neuonc/nos337
|View full text |Cite
|
Sign up to set email alerts
|

Regression of glioma tumor growth in F98 and U87 rat glioma models by the Nitrone OKN-007

Abstract: OKN-007 may be considered as a promising therapeutic addition or alternative for the treatment of aggressive human gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 26 publications
4
65
0
Order By: Relevance
“…Our data also suggest that the inhibition of the tumor growth by OKN-007 in different preclinical glioma models, as we have reported previously [810], may in part be due to the reduction of free radicals, as demonstrated in this study on F98 gliomas. IHC assessment of commonly studied tumor markers for cell proliferation or differentiation, hypoxia, angiogenesis, and apoptosis indicated that OKN-007 was able to significantly decrease cell proliferation (glucose transporter 1 (Glut-1) and the cell proliferation marker, MIB-1) but not cell differentiation (carbonate anhydrase IX), decrease angiogenesis (microvessel density (MVD; measured as levels of the endothelial marker, CD-31), but not the VEGF), decrease HIF-1α, and increase apoptosis (cleaved caspase 3) compared with untreated controls [8]. OKN-007-induced decreases in Glut-1 and HIF-1α levels seemed to be similar in both F98 and U87 glioma models, whereas increased apoptosis seemed to be more elevated in the F98 gliomas compared to the U87 tumors [8].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our data also suggest that the inhibition of the tumor growth by OKN-007 in different preclinical glioma models, as we have reported previously [810], may in part be due to the reduction of free radicals, as demonstrated in this study on F98 gliomas. IHC assessment of commonly studied tumor markers for cell proliferation or differentiation, hypoxia, angiogenesis, and apoptosis indicated that OKN-007 was able to significantly decrease cell proliferation (glucose transporter 1 (Glut-1) and the cell proliferation marker, MIB-1) but not cell differentiation (carbonate anhydrase IX), decrease angiogenesis (microvessel density (MVD; measured as levels of the endothelial marker, CD-31), but not the VEGF), decrease HIF-1α, and increase apoptosis (cleaved caspase 3) compared with untreated controls [8]. OKN-007-induced decreases in Glut-1 and HIF-1α levels seemed to be similar in both F98 and U87 glioma models, whereas increased apoptosis seemed to be more elevated in the F98 gliomas compared to the U87 tumors [8].…”
Section: Discussionsupporting
confidence: 89%
“…OKN-007 is a small molecule that can traverse the blood–brain barrier, and has anti-inflammatory, antioxidant, and proapoptotic properties [1136]. Our group has also established that OKN-007 is an effective anticancer agent in rodent preclinical glioma models [810], and it is currently undergoing clinical trial assessment as a new investigational drug for recurrent adult glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the tumoral central core could have had areas of necrosis with hypoxia which would cause decreased expression of luciferase. 39 The imaging information of in vivo BLI in Fischer344/F98 luc model is in good compliance with a previous report in the literature. 40 In short, the well-established Fischer344/F98 luc model can provide convenient, rapid, and non-invasive monitoring of the orthotopic tumor growth.…”
supporting
confidence: 88%